PENINGKATAN KECEPATAN DAN KELANCARAN MEMBACA AL QUR'AN MELALUI INTENSITAS PENGGUNAAN METODE QIRO’ATI DI TPQ NURUL ISLAM KABUPATEN PROBOLINGGO - Sabila Almas Kistina; Nailul Izzah; Athiyah Ilahiyah (PT. Sulthan Journal Publisher, 2026)
This study aims to improve the speed and fluency of Qur'an reading through the intensive use of the Qiroati method among students at TPQ Nurul Islam. The research employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages conducted in two cycles. The subjects of this study were 15 second-level students. Data were collected through observation and reading tests, while data analysis used descriptive quantitative and qualitative approaches. The results showed a significant improvement in students’ Qur'an reading ability. In the pre-cycle stage, learning mastery was only 20%, with most students categorized as low. In cycle I, mastery improved to 60%, indicating progress in the good category. Furthermore, in cycle II, learning mastery increased significantly to more than 80%, with most students achieving good and very good categories. This improvement indicates that the intensive application of the Qiroati method is effective in enhancing students’ reading speed and fluency. Therefore, the Qiroati method can be considered an effective instructional strategy for improving Qur'an reading skills among TPQ students.